Drug Value of Drynariae Rhizoma Root-Derived Extracellular Vesicles for Neurodegenerative Diseases Based on Proteomics and Bioinformatics. (31st December 2022) - Cao, Yue; Zhao, Qing; Liu, Fubin; Zheng, Lei; Lin, Xingdong; Pan, Mingyue; Tan, Xuejun; Sun, Ge; Zhao, Kewei
ABSTRACT: Extracellular vesicles (EVs) are nano-sized membrane vesicles released by various cell types. Mammalian EVs have been studied in-depth, but the role of plant EVs has rarely been explored. For the first time, EVs from Drynariae Rhizoma roots were isolated and identified using transmission electron microscopy and a flow nano analyzer. Proteomics and bioinformatics were applied to determine the protein composition and complete the functional analysis of the EVs. Seventy-seven proteins were identified from Drynariae Rhizoma root-derived EVs, with enzymes accounting for 47% of the proteins. All of the enzymes were involved in important biological processes in plants. Most of them, including NAD(P)H-quinone oxidoreductase, were enriched in the oxidative phosphorylation pathway in plants and humans, and Alzheimer's disease, Huntington's disease, and Parkinson's disease, which are associated with oxidative stress in humans. These findings suggested that EVs from Drynariae Rhizoma roots could alleviate such neurological diseases and that enzymes, especially NAD(P)H-quinone oxidoreductase, might play an important role in the process. Graphical abstract: uf0001